2018
DOI: 10.1007/s12630-018-1181-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between albumin administration and survival in cardiac surgery: a retrospective cohort study

Abstract: In this large retrospective study, use of 5% albumin solution was associated with significantly decreased odds of in-hospital mortality and all-cause 30-day readmission rate compared with administration of crystalloids alone in adult patients undergoing on-pump cardiac surgery. These results warrant further studies to examine fluid receipt, including 5% albumin, in surgical populations via randomized-controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 40 publications
0
23
0
5
Order By: Relevance
“…The low albumin has been associated with adverse outcomes in various other disease conditions [18][19][20][21][22][23], as well as in COVID-19 patients who were hospitalized [9,10,24]. Kheir et al concluded in their study that higher albumin level on admission was associated with favorable outcomes in hospitalized COVID-19 patients [11].…”
Section: Plos Onementioning
confidence: 99%
“…The low albumin has been associated with adverse outcomes in various other disease conditions [18][19][20][21][22][23], as well as in COVID-19 patients who were hospitalized [9,10,24]. Kheir et al concluded in their study that higher albumin level on admission was associated with favorable outcomes in hospitalized COVID-19 patients [11].…”
Section: Plos Onementioning
confidence: 99%
“…71,72 However, clear evidence of benefit is also lacking, and any benefits may be limited to specific patient populations. [73][74][75]…”
Section: Methods Of Fluid Administrationmentioning
confidence: 99%
“…The results from previous studies on cardiac surgical patients regarding mortality associated with type of fluid used are inconclusive. A retrospective study of 2,190 propensity matched cohort of cardiothoracic surgical patients demonstrated a lower in-hospital mortality and all-cause 30-day readmission with albumin use when compared with crystalloids ( 33 ). Another retrospective study that utilized a large database of 19,578 patients who underwent coronary artery bypass grafting surgery indicated lower all-cause mortality with albumin use (OR, 0.80; 95% CI, 0.67–0.96) ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…by the study by Sedrakyan et al ( 34 ) may still confound their results. One of the previous studies also excluded patients with missing data ( 33 ) but do not report this proportion of patients, and the other ( 34 ) does not mention missing data at all. Further, the exact indications (e.g., hypotension, low urine output, low central venous pressure, and high lactate) for albumin use could not be determined due to the retrospective nature of our study.…”
Section: Discussionmentioning
confidence: 99%